PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VA SD NEGERI 37 PEKANBARU - Kasniwati, Kasniwati; Noviana, Eddy; Zufriady, Zufriady (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was motivated by the low social studies learning outcomes of VA students in SDN 37 Pekanbaru on social studies subject. Can be seen from the determined KKM is 75, from 32 students who reached the KKM were 15 people (46.87%) and those who did not reach the KKM were 17 people (53.12%) with a class average of 71.56. This study aims to know the teacher activities, student activities and student learning outcomes in learning through the TSTS model on social studies subject in VA students at SDN 37 Pekanbaru. This research is a classroom action research, this research was conducted in SDN 37 Pekanbaru. The subjects in this study were VA class with 32 students. This study was conducted in two cycles with four steps, such as: planning, implementation, observation and reflection. The results of this study announced after applying the TSTS type cooperative learning model can improve social studies learning outcomes. This can be proven by: teacher activity in the first cycle of 62.5% in the second cycle 83.33%. The activity of students in the first cycle obtained 58.33%, in the second cycle was 83.33. Learning outcomes at the base score were 71.56, increasing in the first cycle of 75.93 and in the second cycle of 86.25. Based on the results of this study, it can be concluded that the application of the cooperative learning model of the TSTS type can improve the social studies learning outcomes in VA class at SDN 37 PekanbaruKey Words: Cooperative Learning Model TSTS type, Social Studies Learning Outcomes